Examining the incentive effects of food aid on household behavior in rural Ethiopia - Hoddinott, John F. (International Food Policy Research Institute, 2004)
In Ethiopia, while superficial examination suggests strong disincentive effects of food aid on labor supply and agricultural activities, these largely vanish under more careful statistical analysis." -- from Text